Urban and rural stroke mortality rates in China between 1988 and 2013: An age-period-cohort analysis. (April 2017) - Li, Jingjing; Li, Boyang; Zhang, Fengfan; Sun, Yang
Objective: To evaluate effects attributable to age, time period and birth cohort, on stroke mortality data from urban and rural regions in China between 1988 and 2013. Methods: Mortality data were obtained from the Chinese Health Statistics Annual Report (1987–2001) and Chinese Health Statistics Yearbooks (2003–2014). Population data were obtained from population censuses (i.e. 1982, 1990, 2000 and 2010). Data were analysed using an age-period-cohort (APC) model and intrinsic estimation (IE) method. Results: The age effect suggested that all older residents had higher stroke mortality risk than younger residents. Period effect showed that compared with figures for 1988, stroke mortality in 2013 was 1.8 times higher for urban regions and 2.4 times higher for rural regions. After controlling for age and period effects, cohorts born before the Chinese economic reform had a steady decline in stroke mortality. However, mortality rates increased and fluctuated in post-reform cohorts. Conclusions: This APC-IE analysis identified a modest period effect with large age and cohort contributions to both the overall mortality and the disparity between urban and rural stroke mortality. Identifying early life and cumulative risk factors for stroke, improving equality in stroke prevention and care are needed to reduce the stroke mortality in China.